2018
DOI: 10.1016/j.jor.2018.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive versus conventional approaches in total knee replacement/arthroplasty: A review of the literature

Abstract: MIS approaches seem to provide advantages in the immediate post-operative period accompanied by increased reports of complications. Consequently, further investigation based on large well-designed studies with long-term results are warranted to further clarify MIS effectiveness/safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…This approach closes with restoration of the anatomy that results in a robust double-layered watertight seal closure of the proximal half of the arthrotomy, which enables or tolerates an aggressive postoperative patient behavior, knee ROM or function [ 7 ]. Although the advantages of a specific surgical approach in the knee arthroplasty have been a controversial topic, several studies have shown that with quadriceps-sparing approaches that patients may possibly have a quicker rehabilitation in the short term, which may therefore enhance outpatient knee arthroplasty [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This approach closes with restoration of the anatomy that results in a robust double-layered watertight seal closure of the proximal half of the arthrotomy, which enables or tolerates an aggressive postoperative patient behavior, knee ROM or function [ 7 ]. Although the advantages of a specific surgical approach in the knee arthroplasty have been a controversial topic, several studies have shown that with quadriceps-sparing approaches that patients may possibly have a quicker rehabilitation in the short term, which may therefore enhance outpatient knee arthroplasty [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Faced with an aging population, the prevalence of OA is increasing, and joint replacement surgery is becoming more common. 86,87 Postsurgical complications include instability, infection, fracture, and loosening, and the ability to discriminate between infection and aseptic loosening has important implications for patient management. [88][89][90][91] The first-line modality after hip or knee arthroplasty is radiography, which can show subsequent fractures and dislocations.…”
Section: Orthopedic Complicationsmentioning
confidence: 99%
“…Possible problems with the surgical technique include its steep surgical learning curve, longer operative time, compromised surgical exposure, technical errors (e.g. fracture or component malposition), and neurovascular damage [5][6][7][8][9][10][11]. Several authors expressed concerns that MIS approaches may lead to component misalignment [12] and perioperative complications such as local wound-related problems, deep venous thrombosis (DVT) and pulmonary embolism (PE) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%